PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP HASIL BELAJAR DAN KEAKTIFAN SISWA - Jannah, Liwaul; Pratiwi, Siska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to empirically investigate the effect of implementing the Snowball Throwing cooperative learning model on students' science learning outcomes and learning activity. This quantitative research employed a pre-experimental method with a One-Group Pretest-Posttest Design. The research population and sample consisted of 25 third-grade students (class 3A) at SDN Pejagan 3 Bangkalan for the 2025/2026 academic year, selected using total sampling. Data collection instruments included a 15-item multiple-choice cognitive test to measure learning outcomes and a 15-item Likert-scale questionnaire to assess student activity. The collected data were analyzed using paired sample t-tests via IBM SPSS version 21.0. The descriptive analysis revealed that the mean score for science learning outcomes increased significantly from 51.44 in the pretest to 74.44 in the posttest. Concurrently, the mean score for student learning activity rose from 26.04 to 33.20. The inferential statistical analysis yielded a significance value of 0.000 (p < 0.05) for both variables, leading to the rejection of the null hypothesis. In conclusion, the implementation of the Snowball Throwing learning model exerts a significant positive effect on enhancing both the cognitive learning outcomes and the learning activity of elementary school students in science education.